2000
DOI: 10.1007/s001470050703
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C - an accurate marker of glomerular filtration rate after renal transplantation?

Abstract: The performance of serum cystatin C as a screening marker of reduced creatinine clearance in renal transplantation was evaluated and compared to serum creatinine. In addition we studied whether cystatin C accurately reflects creatinine clearance over the entire range of transplant function. Serum cystatin C, serum creatinine, and creatinine clearance were measured in 110 adult renal transplant recipients. Cystatin C detected reduced creatinine clearance with the high sensitivity of 95 YO. Serum cystatin C and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Most studies of Scyc in kidney transplantation, however, have focused on its ability to estimate GFR during times of stable renal function (11)(12)(13)(14). In a related transplant setting, Herget-Rosenthal et al (37) showed that Scyc detects rapid GFR decreases in live kidney donors after uninephrectomy 1 to 2 days earlier than Scr.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Most studies of Scyc in kidney transplantation, however, have focused on its ability to estimate GFR during times of stable renal function (11)(12)(13)(14). In a related transplant setting, Herget-Rosenthal et al (37) showed that Scyc detects rapid GFR decreases in live kidney donors after uninephrectomy 1 to 2 days earlier than Scr.…”
Section: Discussionmentioning
confidence: 97%
“…Scyc is a 13.4-kDa cysteine protease inhibitor produced by all nucleated cells at a constant rate, undergoes no tubular secretion, and does not return to the circulation after being freely filtered by glomeruli. Its role as an improved marker of glomerular filtration has been extensively studied not only in the setting of chronic kidney disease (8 -10) but also in kidney transplantation (11)(12)(13)(14). Multiple studies have described the superiority of Scyc for diagnosing filtration failure compared with Scr in the setting of AKI, (15)(16)(17)(18)(19)(20) whereas others have described its independent association with poor outcomes (21)(22)(23)(24)(25).…”
mentioning
confidence: 97%
“…Cys-C appeared to be a potentially better GFR marker than Cr as it is not affected by age, sex, muscle mass and height of the patients [7,8,[21][22][23]. However, Cr measurement is believed to be as efficacious as serum cys-C for the estimation of the GFR after renal transplantation [1,24]. In our study, the diagnostic efficiency of cys-C was superior to that of Cr on the third day of the posttransplantation period.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of serum creatinine (Cr) is currently used for a quick and inexpensive estimation of the glomerular filtration rate (GFR). However, it has some significant disadvantages, such as the inability to indicate renal function impairments of 50% or less [1]. Also, the Cr value is dependent on muscle mass, age, sex and height of the patient.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation